Influential Article Review - A Binomial Compound Option Approach to Modeling Sequential R&D Investments - Carey, Donald; Daugherty, Zayn; Sutherland, Georgie (Journal of Strategic Innovation and Sustainability, 2019)
This paper examines research and development. We present insights from a highly influential paper. Here are the highlights from this paper: In this paper, we propose a binomial approach to modeling sequential R&D investments. More specifically, we present a compound real options approach, simplifying the existing valuation methodology. Based upon the same set of assumptions as prior models, we show that the number of computational steps for valuing any compound option can be reduced to a single step. We demonstrate the applicability of our approach using the real-world example of valuing a new drug application. Overall, our work provides a heuristic framework for fostering the adoption of binomial compound option valuation techniques in R&D management. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.